Effectiveness of Peer Group Education on Breast Self-Examination Skills for Early Detection of Fibroadenoma Mammae: A Quasi-Experimental Study among Adolescent Girls in Indonesia - Andi Tenri Abeng; Sunarti Sunarti; Linda Hardianti Saputri (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2026)
Fibroadenoma Mammae (FAM) is the most common benign breast tumor occurring in adolescent girls and women under 30 years of age. This study aims to determine whether peer group education can significantly enhance students' ability to perform breast self-examination (BSE) as a preventive effort against Fibroadenoma Mammae. This research employed a quasi-experimental design with a one-group pre-test and post-test approach. The study was conducted at State Senior High School 3 Gowa with 50 respondents, consisting of female students from grades X and XI selected through purposive sampling based on inclusion and exclusion criteria. The intervention involved Peer Group Education, where selected students (peer educators) were trained to educate their peers using discussion sessions, video demonstrations, and educational tools. Data were collected through questionnaires and observation sheets and analyzed using the Wilcoxon Signed Rank Test to assess differences before and after the intervention. The average pre-test score of early detection skills was 3.46, which increased to 8.60 after the intervention. The Wilcoxon test result showed Z = -6.557 with p = 0.000 (p < 0.05), indicating a statistically significant improvement in early detection skills after the Peer Group Education intervention. In conclusion, Peer Group Education was proven effective in enhancing the early detection skills of Fibroadenoma Mammae among adolescent girls at State Senior High School 3 Gowa. The peer-led approach increased motivation, engagement, and practical understanding, demonstrating that peer-based learning can be a valuable method for promoting adolescent reproductive health awareness.